2014
DOI: 10.4103/0975-2870.128974
|View full text |Cite
|
Sign up to set email alerts
|

Kidney injury molecule-1: A urinary biomarker for contrast-induced acute kidney injury

Abstract: Objective The aim of the present study is to evaluate the urinary KIM-1 level in the patients after 24 h angiography as a predictive biomarker of contrast-induced acute kidney injury. Methods This study included 80 selective patients attending in the cardiology unit (48 males, 32 females). The study was conducted in the cardiac catheterization unit at Al-Hussein Medical City/ Kerbala. Clinical examination and laboratory investigations were made before and 24 h after angiography, these investigations include: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…It has been suggested that KIM-1 plays an important role in regenerating damaged epithelial cells and in removal of dead cells fom the tubular lumen by phagocytosis [53,55]. KIM-1 is found in the urine as early as 24 h after coronary angiography (using the iso-osmolar contrast medium iodixanol or the low-osmolar contrast medium iopromide), while eGFR (based on SCr) did not change significantly during the first 48 h after contrast administration [57]. In adult patients undergoing cardiac surgery, urinary KIM-1 could predict the development of AKI much more than NGAL [58,59].…”
Section: Kim-1mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that KIM-1 plays an important role in regenerating damaged epithelial cells and in removal of dead cells fom the tubular lumen by phagocytosis [53,55]. KIM-1 is found in the urine as early as 24 h after coronary angiography (using the iso-osmolar contrast medium iodixanol or the low-osmolar contrast medium iopromide), while eGFR (based on SCr) did not change significantly during the first 48 h after contrast administration [57]. In adult patients undergoing cardiac surgery, urinary KIM-1 could predict the development of AKI much more than NGAL [58,59].…”
Section: Kim-1mentioning
confidence: 99%
“…In clinical practice, urinary L-FABP is a good biomarker for AKI in cisplatin-induced nephrotoxicity [118], in septic shock induced AKI [78,119], in contrast-induced AKI [120][121][122][123][124][125], in AKI occurring in patients undergoing percutaneous coronary intervention due to unstable angina [84], in AKI following cardiac surgery [118,126], in AKI of patients admitted to the Intensive-Care Unit with sepsis [127], in AKI occurring in pediatric patients following cardiopulmonary bypass surgery [64], in AKI of human kidney transplant patients from living-related donors [35,116]. Under these conditions, urinary L-FABP is detected much earlier than the rise in SCr.…”
Section: L-fabpmentioning
confidence: 99%
“…133 Urinary levels of the L-FABP have been shown to increase in patients who develop AKI after exposure to IV CM. [133][134][135][136][137] Bachorzewska-Gajewska et al 112 studied 25 patients with normal serum creatinine who underwent PCI for unstable angina: urinary L-FABP increased significantly, like urinary NGAL, after 4 hours and remained elevated up to 48 hours.…”
mentioning
confidence: 99%
“…67,69 The use of urinary KIM-1 as a biomarker of AKI is based on the fact that there is no KIM-1 expression in the kidneys of healthy subjects, and on its upregulation in the apical cell membrane of tubules during AKI. 67 Vijayasimha et al 70 have carried out a study to evaluate whether KIM-1 allows the identification of CI-AKI earlier than the rise in serum creatinine. The study involved 100 consecutive patients with normal serum creatinine undergoing angiographic procedure.…”
mentioning
confidence: 99%
“…Na prática clínica, a L-FABP tem sido capaz de diagnosticar a LRA antes mesmo da creatinina sérica em pacientes com nefrotoxicidade induzida por cisplatina (Negishi et al 2009), em choque séptico (Nakamura et al 2009;Tsuchimoto et al 2014), após uso de contraste (Nakamura et al 2006;Vijayasimha et al 2013), após cirurgia cardíaca (Katagiri et al 2012) em pacientes de UTI com sepse (Doi et al 2010) e em transplantados renais (Yamamoto et al 2007b). A L-FABP parece ser um biomarcador de lesão renal no geral, pois também se mostrou alterada em pacientes com DRC (Kamijo et al 2006).…”
Section: L-fabpunclassified